Women’s Political Participation in Islamic Law: A Case Study of The West Aceh Legislative Council - Kurdi, Akhmad Ikraam (Al-Risalah, 2025)
Women's involvement in politics at the national and local levels is an important aspect of democratic state administration. However, there is still a narrative that suggests that women should not be leaders because it is considered incompatible with Islamic principles. This study aims to analyze women's involvement in politics based on the perspective of Islamic law and to find out the reality of women's involvement in politics in the West Aceh District House of Representatives (DPRK). Using empirical legal research methods and a sociological approach, this study found that Islamic law actually allows women to be involved and occupy political positions in various lines of power if the aim is to achieve the public interest, as stated in Surah An-Nisa' verse 26. Women's involvement in politics can increase policy inclusiveness and realize gender equality. However, the reality on the ground shows that women's involvement in politics in the West Aceh DPRK is still low, at only 12% for the 2024-2029 period, far below the 30% threshold specified in Article 245 of the General Election Law. This is due to several factors, including a strong patriarchal culture, lack of support from political parties for female candidates, and inappropriate religious interpretations. Therefore, this study recommends the need for a more in-depth study of the Quran and hadith with attention to gender equality aspects, as well as advocacy to raise awareness of the importance of women's involvement in politics.